Analysis of Female BMX Cross Athletes' Self Confidence and Anxiety Based on Menstrual Cycle - Lucky Muhammad Rizky; Rere Anne (Journal of Physical Education Health and Sport, 2025)
In high-intensity sports such as BMX Cross, psychological factors such as anxiety play a significant role in influencing athlete performance. In female athletes, the menstrual cycle can cause hormonal changes that impact physical and psychological conditions, including increased anxiety. Each cycle phase—follicular, ovulatory, and luteal—has different potentials to trigger emotional responses, influencing an athlete’s perception of readiness and performance during competition. This study aimed to understand the role of self-confidence and anxiety in female BMX Cross athletes during the menstrual cycle. This study uses a descriptive quantitative approach with a correlational design. The sample consisted of 22 female BMX Cross athletes. The instrument used was a self-confidence and anxiety questionnaire, given once to all respondents. The study's results showed a significant relationship between self-confidence and anxiety levels during the menstrual cycle. Physiological hormonal changes, physiological factors, and psychological factors such as self-perception and previous experiences affect the mental condition of athletes. This study concludes that, based on the menstrual cycle, the self-confidence and anxiety of female BMX Cross athletes are related. Therefore, a deeper approach is needed in athlete coaching to help athletes manage self-confidence and anxiety and maintain optimal performance. Therefore, we recommend paying more attention to athletes' menstrual cycles in training planning and match strategies to help maintain optimal athlete performance.